Os programas eleitorais do Segundo Turno das Eleições Presidenciais de 2014: uma análise comportamental - Pasquinelli, Renata de Souza Huallem (2015)
Based on the proposed analysis of socially constructed knowledge and social representations in a Behavior Analytic perspective (Guerin, 1992) and on studies that analyze the role of the media in this process, the present study analyzed the second round electoral programs of the 2014 presidential elections. The questions that guided the analysis was to evaluate if the print media and the voting polls affect the content of electoral programs, identify differences in verbal responses of the candidates as the responses resemble tacts, intraverbals or use of subject repetition. The programs were divided into scenes and these scenes were classified as: speakers, pictures, themes, valuation and whether they were positive or negatives. The main results were: there is interference of the press headlines on the topics covered in the electoral program; the voting polls control to which listener the electoral program is intended to, the programs show differences in the responses that could be tacts, intraverbals or use of scenes repetition. From the analysis of the data it is concluded that depending on these differences (between the programs) one electoral program can be more efficient than the other in changing the voter behavior